Pengaruh Corporate Governance, Kepemilikan Asing Dan Audit Tenure Terhadap Integritas Laporan Keuangan - May Wulandari; Erna Hernawati; Husnah Nur Laela Ermaya (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The research is a quantitative research in order to know the influence of audit committee, indepedendent commissioner, foreigh ownership and tenure audit towards financial statements integrity. Path analysis is analytical technique being used, software used is smartpls 3.2.2 with 5% level of significance. Testing shows results (1) audit committee gave negative effect to financial statements integrity, (2) independent commissioner gave no effect to financial statements integrity, (3) foreigh ownership also gave no effect to financial statements integrity, (4) tenure audit gave positive effect to financial statements integrity. Keyword: Audit Committee, Independent Commissioner, Foreign Ownership Audit Tenure, Integrity Of Financial Statements.